Assessment of climate-smart agricultural practices of plantain farmers in Anambra State, Nigeria (Asian Journal of Agriculture, 2025)
Abstract. Emmanuel OE, Nnenna OM, Nkiruka B-CG, Anulika UO, Thankgod EK, Angela ON, Nwuguru NR, Ekunyi UN, Ighokpozi OE, Ajah OE, Chinenyenwa T-AA, Olivia OC, Marylilian OO, AGU OP, Rhoda IT, Ojochenemi I, Chukwuka CC. 2025. Assessment of climate-smart agricultural practices of plantain farmers in Anambra State, Nigeria. Asian J Agric 9: 140-149. The study examined the climate-smart agricultural practices of plantain farmers in Anambra State, Nigeria. The study used a multistage sampling technique to select 76 plantain farmers. A structured questionnaire was used for primary data collection, and mean, descriptive statistics, multivariate probit regression, and factor analysis models were employed in the analysis. The result shows that the plantain farmers were middle-aged (46 years), females (59.2%), married (53.9%), with a household size of 7 persons and farming experience of 18 years. The result further shows that 75% of the plantain farmers were aware of climate change. Climate-smart agricultural (CSA) practices adopted include mixed farming (80.3%), movement to different sites (68.4%), planting of early maturing variety (86.8%), crop rotation (88.2%), and application of farm yard manure (71.1%). Age, gender, level of education, household size, farm size, farming experience, extension contacts, credit use, and victim of climate events statistically influenced the adoption of CSA practices. Problems of capital, soil fertility, lack of technical know-how, poor extension access, lack of timely information on weather conditions, instability in the planting calendar, high cost of inputs, and limited lands constrained plantain production and adoption of CSA practices. Efforts should be made to provide farmers with training and workshops on climate-smart agricultural practices; this will enhance their knowledge to make informed decisions in adopting CSA practices in mitigating climate change.
Keywords: Agricultural practices, assessment, climate-smart, plantain farmers